Vector competence and feeding-excretion behavior of Triatoma rubrovaria (Blanchard, 1843) (Hemiptera: Reduviidae) infected with Trypanosoma cruzi TcVI. - Thaiane Verly; Stephanie Costa; Nathanielly Lima; Jacenir Mallet; Francisco Odêncio; Mirian Pereira; Carlos José de Carvalho Moreira; Constança Britto; Márcio G Pavan (Public Library of Science (PLoS), 2020)
Background Several studies addressed changes on the insect vector behavior due to parasite infection, but little is known for triatomine bugs, vectors of Trypanosoma cruzi, the etiological agent of Chagas disease. We assessed infection rates and metacyclogenesis of T. cruzi (TcVI) in fifth-instar nymphs of Triatoma rubrovaria comparing with the primary vector Triatoma infestans. Also, biological parameters related to feeding-excretion behavior were evaluated aiming to identify which variables are most influenced by T. cruzi infection. Methodology/principal findings Fifth-instar nymphs of T. rubrovaria and T. infestans were fed on mice infected with T. cruzi (TcVI). We compared the presence and the number of parasite evolutive forms in excreta of both triatomine species at 30, 60 and 90 days post-infection (dpi) with traditional statistical analyses. Moreover, both species were analyzed through generalized linear models and multinomial logistic regression hypotheses for seven behavioral parameters related to host-seeking and feeding-excretion. Triatoma rubrovaria and T. infestans had similar overall infection and metacyclogenesis rates of T. cruzi TcVI in laboratory conditions. Regarding vector behavior, we confirmed that the triatomine's tendency is to move away from the bite region after a blood meal, probably to avoid being noticed by the vertebrate host. Interspecific differences were observed on the volume of blood ingested and on the proportion of individuals that excreted after the blood meal, revealing the higher feeding efficiency and dejection rates of T. infestans. The amount of ingested blood and the bite behavior of T. rubrovaria seems to be influenced by TcVI infection. Infected specimens tended to ingest ~25% more blood and to bite more the head of the host. Noteworthy, in two occasions, kleptohematophagy and coprophagy behaviors were also observed in T. rubrovaria. Conclusions/significance Laboratory infections revealed similar rate of T. cruzi TcVI trypomatigotes in excreta of T. rubrovaria and T. infestans, one of the most epidemiological important vectors of T. cruzi. Therefore, TcVI DTU was able to complete its life cycle in T. rubrovaria under laboratory conditions, and this infection changed the feeding behavior of T. rubrovaria. Considering these results, T. rubrovaria must be kept under constant entomological surveillance in Rio Grande do Sul, Brazil.